OPTIMISING MARKETING RESOURCE ALLOCATION THROUGH ACCOUNTING ANALYSIS - Loso Judijanto; Nur Hikmah Huba (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Optimisation of marketing resource allocation through accounting analysis is an important approach to maximising the effectiveness and efficiency of marketing efforts. This research aims to explore how companies can leverage insights from financial data and performance metrics to make data-driven decisions about the allocation of budgets, personnel, and assets across various marketing initiatives and channels. By identifying areas with the highest return on investment, adjusting strategies based on actual results, and continuously refining their approach over time, organisations can ensure optimal use of resources to drive growth, profitability, and competitive advantage. This study emphasises the importance of cross- functional collaboration, clear communication, and a focus on long-term strategic goals in achieving successful optimisation of marketing resource allocation. The findings of this study provide valuable guidance for companies seeking to maximise the impact of their marketing investments and achieve sustainable success in today's increasingly dynamic and competitive marketplace.